Production of biochar from crop residues and its application for biofuel production processes – An overview. (October 2022) - Seo, Jung Yoon; Tokmurzin, Diyar; Lee, Doyeon; Lee, See Hoon; Seo, Myung Won; Park, Young-Kwon
Graphical abstract: Highlights: Crop residues (CR) are promising sustainable feedstocks for biochars and biofuels. CR biochars are produced by pyrolysis and hydrothermal carbonization. CR biochars could be applied in catalytic reactions for biodiesel and biogas. Tar can be cracked using CR biochar and metal-loaded biochar. CR supply, biochar production, and utilization for biofuel production are addressed. Abstract: A sustainable carbon-neutral society is imperative for future generations, and biochars and biofuels are inevitable choice to achieve this goal. Crop residues (CR) such as sugarcane bagasse, corn stover, and rice husk are promising sustainable resources as a feedstock for biochars and biofuels. Extensive research has been conducted on CR-based biochar production not only in environmental remediation areas but also in application for biofuel production. Here, the distribution and resource potential of major crop residues are presented. The production of CR-biochar and its applications in biofuel production processes, focusing on the latest research are discussed. Finally, the challenges and areas of opportunity for future research in terms of CR supply, CR-biochar production, and CR-biochar utilization for biofuel production are proposed. Compared with other literature reviews, this study can serve as a guide for the establishment of sustainable, economical, commercial CR-based biorefineries.